2022
DOI: 10.3389/fmolb.2022.912620
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a novel tumor driver gene signature for diagnosis and prognosis of head and neck squamous cell carcinoma

Abstract: Objective: Head and neck squamous cell carcinoma (HNSCC) is a common heterogeneous cancer with complex carcinogenic factors. However, the current TNM staging criteria to judge its severity to formulate treatment plans and evaluate the prognosis are particularly weak. Therefore, a robust diagnostic model capable of accurately diagnosing and predicting HNSCC should be established.Methods: Gene expression and clinical data were retrieved from The Cancer Genome Atlas and Gene Expression Omnibus databases. Key prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“… 29 Importantly, the potential diagnostic and prognostic role of NAT10 has been revealed in LSCC. 30 , 31 To analyze the functional effects of NAT10 on LSCC cells, we established sh-NAT10 and the negative control sh-NC plasmids to stably interfere with NAT10 expression for loss-of-function assays. Through CCK-8 detection, we identified that the proliferation of two LSCC cells was dramatically weakened by the knockdown of NAT10.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Importantly, the potential diagnostic and prognostic role of NAT10 has been revealed in LSCC. 30 , 31 To analyze the functional effects of NAT10 on LSCC cells, we established sh-NAT10 and the negative control sh-NC plasmids to stably interfere with NAT10 expression for loss-of-function assays. Through CCK-8 detection, we identified that the proliferation of two LSCC cells was dramatically weakened by the knockdown of NAT10.…”
Section: Discussionmentioning
confidence: 99%